Conceptual tensions and practical trade-offs in tailoring implementation interventions - McHugh, Sheena M.; Riordan, Fiona; Curran, Geoff M.; Lewis, Cara C.; Wolfenden, Luke; Presseau, Justin; Lengnick-Hall, Rebecca; Powell, Byron J. (Frontiers in Health Services, 2022)
Tailored interventions have been shown to be effective and tailoring is a popular process with intuitive appeal for researchers and practitioners. However, the concept and process are ill-defined in implementation science. Descriptions of how tailoring has been applied in practice are often absent or insufficient in detail. This lack of transparency makes it difficult to synthesise and replicate efforts. It also hides the trade-offs for researchers and practitioners that are inherent in the process. In this article we juxtapose the growing prominence of tailoring with four key questions surrounding the process. Specifically, we ask: (1) what constitutes tailoring and when does it begin and end?; (2) how is it expected to work?; (3) who and what does the tailoring process involve?; and (4) how should tailoring be evaluated? We discuss these questions as a call to action for better reporting and further research to bring clarity, consistency, and coherence to tailoring, a key process in implementation science.